MRI findings in primary brain lymphoma in immunocompetent patients - Younis, Saeed Nadhim; Abdullah, Aras Rafeiq (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Primary brain lymphoma is an extranodal aggressive intracranial neoplasm of lymphocytic origin originating and confined to the brain parenchyma and meninges. It is rare in immune competent patients, but its incidence is increasing. This retrospective study was conducted to record the MRI features of primary brain lymphoma at the time of diagnosis in immunocompetent patients. Methods: Of the 450 patients diagnosed with the brain tumor during a period of five years from 2008 to 2013, the clinical features and MRI findings of 16 cases of pathologically proven to be non-Hodgkin’s lymphoma were studied. All the patients were tested negative for HIV and there was no history of immune suppression drugs or any other chronic illness. All the patients were examined with MRI observing the tumor location, multifocality, signal intensity in different sequences, enhancement patterns, peritumoral edema, the presence of hemorrhage and calcification. Results: Of the 16 patients, including the monofocal and multifocal cases, 30 lesions exhibited. The mean age at diagnosis was 53 years. Nine patients (56.25%) found to have a multifocal disease. In more than 75% of lesions, MRI was hypo to iso signal on T1 and T2. Mild to moderate perilesional edema, strong contrast enhancement and restricted diffusion were seen in all cases. The hemorrhagic tumor was noticed in four lesions (13.3%). No calcification and no leptomeningeal lesions were noted. The MRI images in post steroid therapy were studied within one month of treatment. Tumour regression was noticed in 21/30 (70%), stable in 3/30 (10%) and progressing in 6/30 (20%). Conclusion: MRI is a reliable imaging technique in the management of patients with primary brain lymphoma. Early accurate diagnosis is crucial to avoid the unnecessary operation and shift patients from extensive surgery to chemoradiotherapy.